AN ASSESSMENT OF SCIENCE PROCESS SKILLS AMONG STUDENTS: A STUDY OF THE ENUGU STATE POST-PRIMARY EDUCATION SYSTEM - Ezechi, Grace N. (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2022)
The present study assessed junior secondary school students' basic and integrated science process skills. The study was conducted during the 2021/2022 academic year in the post-primary education zones of Enugu state, Nigeria. The participants completed a self-report measure of the SPS. A descriptive research method was adopted in the study. The percentage analysis conducted on the data revealed that most of the respondents (66.2%) showed more familiarity with the concept of basic science process skills than the (33.8%) of their counterparts. Conversely, the result revealed a high level of unfamiliarity with integrated science process skills among the students (84.4%). The finding revealed a gap in the teaching and learning of science in the post-primary education system of Enugu state. It is recommended that teachers improve their pedagogical strategies in the science classroom. The result has implications for developing science education.